2014
DOI: 10.1167/iovs.14-15415
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Autologous Bone Marrow CD34+ Cell Therapy for Ischemic and Degenerative Retinal Disorders: Preliminary Phase 1 Clinical Trial Findings

Abstract: Intravitreal autologous BM CD34+ cell therapy appears feasible and well tolerated in eyes with ischemic or degenerative retinal conditions and merits further exploration. (ClinicalTrials.gov number, NCT01736059.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
1
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(120 citation statements)
references
References 28 publications
2
111
1
6
Order By: Relevance
“…Siqueria RC et al 2 have demonstrated that intravitreal autologous BM stem cell transplantation for hereditary retinal dystrophy has no detectable structural or functional toxicity for over 10 months. Park SS et al 4 have also reported that intravitreal autologous BM stem cell therapy appears to be feasible and well tolerated in eyes with ischemic or degenerative retinal disease during a 6-month follow-up. However, these results are limited to small case numbers with relative short period of follow-up time without data for long-term complications.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Siqueria RC et al 2 have demonstrated that intravitreal autologous BM stem cell transplantation for hereditary retinal dystrophy has no detectable structural or functional toxicity for over 10 months. Park SS et al 4 have also reported that intravitreal autologous BM stem cell therapy appears to be feasible and well tolerated in eyes with ischemic or degenerative retinal disease during a 6-month follow-up. However, these results are limited to small case numbers with relative short period of follow-up time without data for long-term complications.…”
Section: Discussionmentioning
confidence: 96%
“…Cells that have been studied include adult mesenchymal stem cells, [2][3][4]8,9 embryonic stem cells (ESC), [10][11][12][13] and induced pluripotent stem cells (iPS). 14,15 Recent studies have questioned the potential of autologous mesenchymal stem cell transplantation for retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of adult-derived stem cells includes those from the mammalian ciliary body [155,156], cell lines derived from Müller glia [157,158] and non-retinal cells such as mesenchymal stromal cells (MSCs) from bone marrow or adipose tissue [151]. MSCs are currently in clinical trials for other areas of cell transplantation research, and are being employed in a clinical phase I/II study for AMD as a source of factors providing neuroprotection [159]. Human induced pluripotent stem cells (hiPSCs) are a relatively new source of stem cells developed from the direct reprogramming of somatic cells to a pluripotent state [153,160].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Non-retina associated cell types such as mesenchymal stromal cells (MSCs) [151,159,189], neural progenitor cells [190,191], and even dental pulp cells [150] have been transplanted to the retina in order to provide trophic support to the endogenous cells. There are several ongoing clinical trials using adipose stem cells, neural stem cells, and bone marrow stem cells but to date these have not yet yielded results.…”
Section: D) Non-retinal Cell Typesmentioning
confidence: 99%